2012
DOI: 10.1021/nn204116u
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Nanohydrogel Particles as Potential siRNA Carriers for Cellular Delivery

Abstract: Oligonucleotides such as short, double-stranded RNA (siRNA) or plasmid DNA (pDNA) promise high potential in gene therapy. For pharmaceutical application, however, adequate drug carriers are required. Among various concepts progressing in the market or final development, nanosized hydrogel particles may serve as novel transport media especially for siRNA. In this work, a new concept of synthesizing polymeric cationic nanohydrogels was developed, which offers a promising strategy to complex and transport siRNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
172
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(177 citation statements)
references
References 83 publications
2
172
0
3
Order By: Relevance
“…In analogy to earlier reports [22] In analogy to earlier reports [22], a Schlenk tube equipped with a stir bar was loaded with PFPMA (2.0 g; 7.932 mmol), CETPA (83.6 mg; 0.317 mmol) and AIBN (5.2 mg; 0.032 mmol). All compounds were dissolved in anhydrous dioxane (2.0 ml).…”
Section: Instrumentationmentioning
confidence: 91%
See 3 more Smart Citations
“…In analogy to earlier reports [22] In analogy to earlier reports [22], a Schlenk tube equipped with a stir bar was loaded with PFPMA (2.0 g; 7.932 mmol), CETPA (83.6 mg; 0.317 mmol) and AIBN (5.2 mg; 0.032 mmol). All compounds were dissolved in anhydrous dioxane (2.0 ml).…”
Section: Instrumentationmentioning
confidence: 91%
“…RAFT CTA 4-cyano-4-[(ethylsulfanylthiocarbonyl) sulfanyl]pentanoic acid (CETPA) and 4-cyano-4-(phenylcarbonothioylthio)pentanoic acid (CPTPA) and the monomers tri(ethylene glycol) methyl ether methacrylate (mTEGMA) and PFPMA were synthesized according to established procedures [22,28]. Amicon ® Ultra-15 centrifugal filters with a MWCO of 3 or 10 kDa were obtained from Merck Millipore.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[267] Pressley et al [611] have reported on an improved methodology for conducting click reactions to form block and cyclic polymers. [227] PFPMA/LMA Ph AIBN 25 70 100 [225] BA Ph AIBN 30 80 ,25 [194] HA Ph ACPA 5 70 100 [240] HA Ph AHPN 5 70 100 [240] BA/NA Ph AIBN 20 80 100 [202] BA C 4 H 9 S AIBN 30 80 ,25 [194] BA C 4 H 9 S AIBN þ BPO 20 þ 2 E 80 100 [194] HPA [596] tBA Poly(tBA)S AIBN -80 100 [597] NIPAm Poly(tBA-b-NIPAm)S AIBN -80 100 [597] tBA/TBBPMA Ph AIBN (20) (80) 100 [598] DAMEA/TFEA C 12 H 25 S AIBN 20 65 100 [599] HADA [194] St Ph AIBN þ BPO 20 þ 2 E 80 100 [194] St C 4 H 9 S AIBN 30 À 100 80 ,60 [194] St C 12 H 25 S AIBN 10 95 92 [393] A Monomer unit adjacent to thiocarbonylthio group. The process makes use of commercially available copper nanoparticles and is performed with microwave irradiation.…”
Section: Click Reactionsmentioning
confidence: 99%